Assessment of a novel flow cytometry technique of one‐step intracellular staining: Example of FOXP3 in clinical samples1. Issue 3 (16th January 2013) - Demaret, Julie; Saison, Julien; Venet, Fabienne; Malcus, Christophe; Poitevin‐Later, Francoise; Lepape, Alain; Ferry, Tristan; Monneret, Guillaume
Abstract: Background: By measuring multiple parameters on a single‐cell basis, flow cytometry is a potent tool to dissect the phenotypes and functions of cell subsets. However, because this technique may be time‐consuming, particularly for intracellular staining, it could be problematic for its use in daily routine or in large cohorts. Recently, a novel reagent has been developed to perform intracellular staining in one step. The objective of our study was thus to assess this new method in comparison with the reference technique by focusing on FOXP3 staining in clinical samples. Methods: Peripheral blood was collected from 15 HIV‐1‐infected patients, 5 critically ill patients, and 5 healthy volunteers and stained using the two different methods. Different subsets of FOXP3 positive cells were investigated by flow cytometry. Results: When comparing results obtained with the two techniques, no statistical differences between the percentages of CD4+FOXP3+, CD4+CD25+FOXP3+, and CD4+CD25+CD127−FOXP3+ cells were observed. Besides, a strong correlation between percentages of CD4+FOXP3+CD25+CD127− lymphocytes measured with both techniques was found in patients ( r : 0.843, P < 0.001, intra‐class correlation coefficient: 0.820, P < 0.001). Importantly, flow cytometry stainings obtained with the one‐step method were very robust with an excellent intra‐assay precision, a better discriminative power and correct stability and reproducibility of the staining even after blood storage. Conclusions: With a strong correlation between the percentages of FOXP3+ Tregs when compared with the reference method, a better staining quality, a shorter realization time and no need of isotype control, this one step procedure may represent an important improvement for a daily routine use of intracellular staining. © 2012 International Clinical Cytometry Society